Low-Carbon Energy in Africa and Latin America Renewable Technologies, Natural Gas and Nuclear Energy - Guerrero-Lemus, Ricardo; Shephard, Les E. (Lecture Notes in Energy, 2017)
XXVI, 369 p. 182 illus., 178 illus. in color.